2022
DOI: 10.1111/jfpe.13972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatments and drying on shrinkage and rehydration kinetics of ginger (Zingiber officinale)

Abstract: In this study, it was aimed to understand the effect of drying temperature (40, 50, and 60 C) and pretreatments such as conventional blanching (60 C for 5 min) (CB), microwave-assisted blanching (430 W for 2 min) (MAB), and ultrasound (amplitude: 60%; time: 15 min) (US) conditions on shrinkage and rehydration behavior of ginger slices. In all treatment combinations, the volumetric shrinkage of ginger slices was well described by the quadratic equation as a function of moisture content. From the experimental st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The control sample resulted in better moisture diffusivity than MW pretreated sample because of the surface hardening which occurred during drying following MW pretreatment. Similar observation was reported by Buvaneswaran et al (2022) who reported that the moisture content of ginger slices increase during the microwave treatment as result of tissue softening. Further, during drying this free moisture is removed rapidly and thermal and moisture stress is generated resulting in surface hardening of ginger.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The control sample resulted in better moisture diffusivity than MW pretreated sample because of the surface hardening which occurred during drying following MW pretreatment. Similar observation was reported by Buvaneswaran et al (2022) who reported that the moisture content of ginger slices increase during the microwave treatment as result of tissue softening. Further, during drying this free moisture is removed rapidly and thermal and moisture stress is generated resulting in surface hardening of ginger.…”
Section: Resultssupporting
confidence: 89%
“…Microwave pre-treatment was carried out using 900 W, 2540 MHz household microwave system (IFB). 100 g of ginger slices was treated at the power level of 360 W for the duration of 5 min (Buvaneswaran et al, 2022). After that, the pretreated samples were kept in the drier system for extraction.…”
Section: Microwavementioning
confidence: 99%
“…The color parameters L *, a *, and b * values ( L *–lightness to darkness, a *–redness to greenness, and b *–yellowness to blueness) of millet flour were determined using Hunter lab colorimeter (Colourflex EZ model: 45/0). The color differences (Δ E ) between the WFM flour (WFMF) were calculated using a formula defined by Buvaneswaran et al (2021). ΔE=()Lgoodbreak−L*2+()agoodbreak−a*2+()bgoodbreak−b*2 …”
Section: Methodsmentioning
confidence: 99%
“…Color parameters were determined as described by Buvaneswaran et al (2021) using Hunter Lab Colorimeter (Colorflex EZ model: 4510, Hunter Associates Laboratory, Reston, VA). The CIE laboratory coordinates ( L *, a *, and b *) were directly read with a colorimeter.…”
Section: Methodsmentioning
confidence: 99%